CROS FLOW AS TURBINE POWER PLANT MINIHIDRO (PLTM) VILLAGE TO SELF ENERGY - Kosjoko Kosjoko (INFO-TEKNIK, 2015)
Electrical energy provided by the State Electricity Company (PT PLN) until now still not felt equally by the people, especially the rural communities far from the reach of the electricity grid. Some villages are not reached by electricity from the State Electricity Company has the potential micro hydro or mini micro hydro who have used.  Because of these problems in doing an effort to supply needs electrical energy by making use of the conditions and potentials exist in the area. Renewable energy is energy generated from natural sources such as solar, wind and water that can be generated again and these resources will always be available and there is no negative impact on the environment, renewable energy alone can differentiate into many different types of renewable energy will but not all can be used as energy in remote regions and rural areas. (ActeWAGL, 2009). Suppose that in an area that has the potential water headnya made sufficient for power generation, then in the area can be installed powerhouse that adjusts to the size of head available. Energy itself has an important role in achieving the objectives of social, economic and environment for sustainable development as well as a supporter for the national economy. Research leading to the development of technology has been widely done primarily related to insufficient electrical energy to remote areas or rural.The research was conducted in line with the advance of the exploitation of natural energy usage in everyday life, especially water energy that is often encountered. The fundamental advantage of natural energy as electrical energy generation which amounts are always available and there is no negative impact on the environment, especially in the surrounding communities. Based on the above, and by aligning science and technology, the authors are keen to address the existing problems. The author intends to take the title "Influence of Variation Total Sudu On the Tools Mini Hydro Power Plant (micro power) To Support Energy Independent Village" .This method in this study researchers conducted a survey of the location and potential of micro power plants in Jember district.From the results of the survey at a location that will get the data taken near the District Jenggawah Renteng plantation Jember. Results of analysis In this study, researchers designed a micro power units that already exist with the re-design of the blade with a capacity of variations in the amount ranging from 1kW to use the scale in Households with usage limits ranging between 100-200 Watts for the public medium. The conclusion of this study can be concluded as follows: With the number of turbine blades 12 can generate power of 700 watts for blade .  Although totaling 8 and 10, can generate 640 watts of power.Keywords: mini-hydro turbines, energy-independent